Ranking Predatory Journals: Solve the Problem Instead of Removing It! - Mehdi Dadkhah; Giorgio Bianciardi (Tabriz University of Medical Sciences, 2016)
Predatory journals are a well-known issue for scholarly publishing and they are repositories for bogus research. In recent years, the number of predatory journals has risen and it is necessary to present a solution for this challenge. In this paper, we will discuss about a possible ranking of predatory journals. Our ranking approach is based on Beall's criteria for detection of predatory journals and it can help editors to improve their journals or convert their questionable journals to non-predatory ones. Moreover, our approach could help young editors to protect their journals against predatory practice. Finally, we present a case study to clarify our approach.